A survey of contextual factors and psychological needs satisfaction as correlates of youth athletes` developmental outcomes in the ethiopian sports academy context - Tadesse, T.; Asmamaw, A.; Mariam, S. H.; Edo, B. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background This study examined the contextual factors associated with psychological need satisfaction (PNS) and the predictability of the PNS components, together with the contextual factors, on the developmental outcomes of elite young athletes in the Ethiopian sports academies, and further identified differences in perception of PNS from a comparative perspective. The study used a cross-sectional survey design applying developmental and PNS theories as guiding frameworks. Samples of elite young Ethiopian athletes participated (n = 257, 47.47% were women with a mean age of 17.44 years and SD = 0.87, and 52.53% were men with a mean age of 18.25 years and SD = 1.14).